First, let's consider some of the equalities associated with taking derivative of composite functions
"\\frac{d}{dx}y^2=2y\u22c5y\u2032"
"\\frac{d}{dx}y'^2=2y'\u22c5y''"
Then, multiplying both sides by "y'"
"y \n\u2032\u2032\n +\u03c9^2\n y=0|| \\times 2y \n\u2032"
we obtain
"2y \n\u2032\n \u22c5y \n\u2032\u2032\n +\u03c9^\n2\n \u22c5(2y \n\u2032\n \u22c5y)=0"
"\\frac{d}{dx}\n\n\u200b\t\n (y'^2\n )+ \n\\frac{d}{dx}\n\n\u200b\t\n (\u03c9^2\n \u22c5y^2\n )=0"
Therefore, applying the sum rule
"\\frac{d}{dx}\n\n\u200b\t\n (y'^2\n +\u03c9^2\n \u22c5y^2\n )=0"
"y'^2\n +\u03c9^2\n \u22c5y^2=C^2"
Resolving this equation we get
"y'=\\pm\\sqrt{C^2-\u03c9^2\n \u22c5y^2}"
"\\frac{dy}{\\sqrt{C^2-\u03c9^2\n \u22c5y^2}}=\\pm dx"
"\\int \\frac{dy}{\\sqrt{C^2-\u03c9^2\n \u22c5y^2}}=\\pm x+C_1"
We introduce a substitution
"u=\\frac{\u03c9\u22c5y}{C}\n\u200b"
"du=\\frac{\u03c9\u22c5dy}{C}"
"\\int \\frac{Cdu}{\u03c9C\\sqrt{1-u^2}}=\\pm x+C_1"
"\\frac{1}{\u03c9}\\arcsin(u)=\\pm x+C_1"
"\\arcsin(u)=\u03c9(\\pm x+C_1)"
"u=\\sin(\u03c9((\\pm x+C_1)))"
"\\frac{\u03c9\u22c5y}{C}=\\sin(\u03c9((\\pm x+C_1))"
"y=\\frac{C}{\u03c9}\\sin(\u03c9((\\pm x+C_1))"
Comments
Leave a comment